Les États-Unis et « l'autre crise » : l'aide extérieure américaine à l'épreuve de la crise alimentaire mondiale - Jean-Baptiste Velut (IdeAs)
According to the United Nations Food and Agriculture Organization (FAO), the increase in food prices in 2007-2008 resulted in poverty and hunger for nearly one hundred million people, raising their number to a tragic record of 1,02 billion people in 2009. Despite the magnitude of this human disaster, the « other crisis » and the political responses aimed at stemming this phenomenon have drawn much less attention from economists and political scientists than the international financial crisis of 2008-2009. This contribution seeks to analyze the policy initiatives undertaken by the US government in response to the food crisis – from George W. Bush to Barack Obama including the key role played by the US Congress. The study of these short-term initiatives is followed by a deeper analysis of the decision-making process of US foreign aid focusing on its objectives, mechanisms and shortcomings.